Entre discursos, mediaciones y representaciones: ‘Las Diabólicas’, un acercamiento hacia el estudio de la violencia de género - Carla Cárdenas Rocuant (Nuevo mundo - Mundos Nuevos, 2008)
This work studies the discourses and representations which appeared during the sixties in the Chilean newspaper Clarin, to refer to women who committed murder against their partners. It analyzes the installation of social imaginaries of violence concerning gender relations and the configuration of feminine and masculine roles from the perspective of the tabloids and mass media, which intended to offer prototypes legitimized by the society.